INVESTIGATING THE STUDENTS’ PEER INTERACTION PATTERN TO COMPREHEND TEXT EXPLANATION IN 3STM CLASSROOM - Nugraheni1, Puteri Ainiyyah; Sumarta, Sumarta; Dewi, Indah Purnama (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is about investigating the students’ peer interaction patterns to comprehend text explanations in the 3STM classroom. Student interaction in group discussions can reveal how well they understand the subject. Students that actively participated in the discussion group displayed a comprehension of the material being discussed. This research employed a descriptive case study. The data was obtained by observation and interviews. The research subjects were 36 students from class XI SMA Negeri in Cikarang Barat, arranged into groups of 5-6 people. This study aims to find what patterns does the students use to deliver their comprehension through group discussion in the 3STM classrooms and what factors cause the patterns to appear. Student interaction is analyzed using the IBIS model by Kunz & Rittel (1970), and there are three elements, namely: issues, positions, and arguments. The 3STM was used in this study to assist students understanding of English texts. The results found that two interaction patterns emerged in this study Detailed Knowledge Exchange and Partial Knowledge Exchange. The emergence of these two patterns was caused by factors such as discussion partners, students' knowledge of the topic being discussed, students' courage in expressing their opinions, and a lack of mastery of English vocabulary and grammar.